(untitled) (Madhyabindu Journal, 2021)
Management accounting is concerned with providing both financial and non-financial information that will help decisions. An understanding of accounting therefore requires an understanding of the decision-making process and an awareness of the users of accounting. The major objective of the study will be to examine the Management accounting practices among Nepalese co-operative organizations. While analyzing the application of management accounting tools practiced in Nepalese co-operative organization for planning, controlling and decision making, it was found that Ratio Analysis, Cash flow statement and capital Budgeting are widely practiced representing. All the co-operative organizations of Nawalpur district a number of co-operatives have been considered as the total population. Till this date there are organizations in Nawalpur in existence. To make the research more reliable, 21 co-operative organizations has been considered for sample population. In average, two techniques were practiced to measure and control overall performance of Nepalese co-operative organization at the end of the year. It seems that 57.15% Nepalese cooperative organization used below average no. of year ending overall performance measuring and controlling techniques.